ERYTROCYTE PFOFAILE AND SURVIVAL OF Pangasius hypophthalmusFED WITHRhizophora apiculata EXTRACT ENRICHED PELLETS - Anderson.s, Roi; Syawal, Henni; Riauwaty, Morina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study aims to look at the description of erythrocyte and tehe ability of feed containing Rhizophora apiculata leaf extract to improve the survival of Siam jambal fish (Pangasius hypophthalmus).The method used is the experimental method with Completely Randomized Design (CRD), one factor with 5 levels of treatment and three replications. Kn: Negative control (feeding without being given R. apiculata leaf extract and without being challenged with A. hydrophila bacteria), Kp: Positive control (feeding without being given R. apiculata leaf extract and tested challenged with A. hydrophila bacteria), P1: Feed containing R. apiculata leaf extract at a dose of 1.5 mg/kg of feed, P2: Dose of 1.6 mg/kg of feed, P3: Dose of 1.7 mg/kg of feed. Siam Jambal fish (P. hypophthalmus) size 8-10 cm is maintained in an aquarium measuring 40×30×30cm with a stocking densities of 1 tail / 3L of water,feeding is done three times a day as much as 10 % of fish body weight.Taking the blood of the tested fishes was done 3 times, namely at the beginning of maintenance, after 30 days of maintenance and 14 days after the test challenged with A. hydrophila. The results of research show that P3 (1.7 mg/kg addition of R. apiculata leaf extract) was the best dose, to improve fish health seen from the final value of total erythrocytes 2.78×106 cells/mm3,hematocrit value 37.00%, and hemoglobin levels from 12.00 g/dL after the challenge test and produce an 80% survival rate.Keywords:Erythrocyte,Hematocrit,Hemoglobin, Pangasius hypophthalmus, Rhizophora apiculata, Aeromonas hydrophila.